(untitled) (Forum Agribisnis, 2017)
Salt is a strategic and high economic valued commodity because it is needed in every human food as a main raw material. The purpose of this research was to analyze marketing channels, function, structure and marketing institutions of farmer salt commodity and to analyze the efficiency of farmer salt marketing in anymarketing channel using marketing margin, farmer’s share and benefit cost ratio approach. The research showed that there were main channels, the formation of which was based on the starting point of the distribution with different institutions, functions and market structure in each channel. The result of operational efficiency analysis indicator and qualitative indicator showed that all marketing channels were inefficient. This was due to the fact that farmers had a role as a price taker and price fixing tended to be unfair because farmer had a weak bargaining power. Thus, goverment role was hoped to change farmers‘roles and improve the presence of farmer groups to increase farmer prosperity.